Open Versus Closed Methods in Treatment of Pilonidal Sinus Disease (Iraqi Journal of Medical Sciences, 2016)
Background: Pilonidal sinus disease can be managed surgically either by excision & primary closure, or by excision and leaving the wound to heal by secondary intention. This study is designed to show the difference between these two methods.Objective: To assess the difference between excision and primary closure versus excision and healing by secondary intention in treatment of pilonidal sinus disease.Methods: Between January 2005 and January 2009, 60 median aged patients with Pilonidal sinus disease were studied in Al-Kadhimiya Teaching Hospital, Baghdad, Iraq; 30 cases were operated by excision and primary closure (group ?); the remaining 30 cases were operated by excision and healing by secondary intention, without closure (group II). The principle outcome measures recorded were duration of hospital stay, operative time, duration of complete healing, wound infection and recurrence rate. Satisfaction and comfort of patient was monitored by using visual analogue scale during first five days post-operatively. Data were statistically analyzed by using SPSS & Chi square.Results: A total of 60 patients were divided into 2 groups, 30 patients operated by using primary closure (group I), and 30 patients operated without closure (group II). Age range of patients was from (16 - 37 yrs). Duration of hospital stay and duration of complete healing was longer in patients of group II than those of group I (p ? 0.001). Operative time in group I is more than that in group II (p ? 0.001). Pain scores were lower in group I than group II (p = 0.004). The frequency of wound infection and recurrence rate after one year follow up were more in group I than group II, this was statistically of little significance.Conclusions: Excision and primary closure is recommended as a preferred procedure in the management of chronic sacral PNS disease. It has the advantages of short hospital stay, early wound healing, rapid return to work.Key words: pilonidal sinus, primary closure, secondary intention
Keywords: pilonidal sinus; primary closure; secondary intention